2005
DOI: 10.1152/ajplung.00250.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pathways for clearance of surfactant protein A from the lung

Abstract: Uptake and degradation of 125 I-surfactant protein A (SP-A) over a 1-h period was studied in alveolar cells in culture and in isolated perfused lungs to elucidate the mechanism for clearance of the protein from the alveolar space. Specific inhibitors of clathrin-and actin-dependent endocytosis were utilized. In type II cells, uptake of SP-A, compared with controls, was decreased by 60% on incubation with clathrin inhibitors (amantadine and phenylarsine oxide) or with the actin inhibitor cytochalasin D. All age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…Although the majority of surfactant phospholipid and protein are removed from the alveolus by ATII cell uptake (49-51), evidence suggests that alveolar macrophages are also important participants in the uptake and degradation of exhausted surfactant protein (52)(53)(54). Uptake by macrophages and ATII cells is mediated predominantly by endocytosis via clathin-coated pits (55,56).…”
Section: Metabolism Of Sp-a/-d In the Normal Lungmentioning
confidence: 99%
“…Although the majority of surfactant phospholipid and protein are removed from the alveolus by ATII cell uptake (49-51), evidence suggests that alveolar macrophages are also important participants in the uptake and degradation of exhausted surfactant protein (52)(53)(54). Uptake by macrophages and ATII cells is mediated predominantly by endocytosis via clathin-coated pits (55,56).…”
Section: Metabolism Of Sp-a/-d In the Normal Lungmentioning
confidence: 99%
“…Unfortunately, these cells in primary culture differentiate relatively rapidly following their isolation and appear to transform into type I cells, which lack the machinery for SP-A synthesis and trafficking. Thus the suitability of these cells for study of the intracellular SP-A trafficking pathways is uncertain.Our prior studies have utilized the isolated perfused lung to evaluate the endocytic uptake (recycling) of radiolabeled SP-A following endotracheal instillation (15,21). These studies have demonstrated disappearance of radiolabeled SP-A from the alveolar space and its appearance in lamellar bodies.…”
mentioning
confidence: 99%
“…Extracellular SP-A appears to play crucial roles in the formation of tubular myelin, in the regulation of lamellar body exocytosis, and in the uptake of phospholipids by endocytosis and their subsequent remodeling (20,23,30,40). The uptake process is dependent on the association of phospholipids with SP-A, followed by binding of the SP-Aphospholipid complex to a specific cell membrane-localized SP-A receptor (4,5,16), and then internalization of the complex by a clathrin-dependent pathway (21,32,35). Although the pathway for uptake of SP-A seems to be fairly well understood, there is uncertainty regarding the pathway for secretion of newly synthesized SP-A by type II cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the protein groups affected were actin-related/cytoskeletal proteins, which was the major group, proteins regulating inflammatory processes, and proteins related to Nrf2-mediated oxidative stress. Of interest, earlier studies have also indicated a role for SP-A in actin filament dynamics via its ability to enhance cell migration and AM chemotaxis [2], phagocytosis [3], other actin-dependent processes [4][5][6] and F-actin assembly [7]. The actin cytoskeleton is highly regulated and dynamic, with globular (G) and filamentous (F) actin, under the influence of many actin binding proteins, constantly changing by polymerization, depolymerization, branching, and remodeling, modulating inflammatory response and oxidative stress ( Figure 1).…”
mentioning
confidence: 99%